2022
DOI: 10.2141/jpsa.0200120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplementation with Dried Neem Leaf Extract on Lipid Peroxidation and Antioxidant Enzyme mRNA Expression in the Pectoralis Major Muscle of Broiler Chickens

Abstract: This study was conducted to evaluate the effects of dietary supplementation of dried neem (Azadirachta indica) leaf extract (DNE) on lipid peroxidation and the expression of genes encoding mRNAs in antioxidant enzymes in the pectoralis major muscle of chickens. A total of 24 male broiler chickens (ROSS308) were divided into three groups (n = 8) at 21 days of age. The control group of chickens was fed a basal diet, and the remaining two groups of chickens were fed a basal diet supplemented with DNE at a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, it ameliorated the negative effects of the cyclical HT. This might be explained by the high free radicalscavenging activity of the DNE (Nakamura et al, 2022). In our previous study, we found that dietary supplementation with 2.0% of DNE significantly increased the expression of genes encoding antioxidant enzymes and reduced the MDA concentration in the breast muscle of broiler chickens kept under thermo-neutral temperature (Nakamura et al, 2022).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…In addition, it ameliorated the negative effects of the cyclical HT. This might be explained by the high free radicalscavenging activity of the DNE (Nakamura et al, 2022). In our previous study, we found that dietary supplementation with 2.0% of DNE significantly increased the expression of genes encoding antioxidant enzymes and reduced the MDA concentration in the breast muscle of broiler chickens kept under thermo-neutral temperature (Nakamura et al, 2022).…”
Section: Resultsmentioning
confidence: 92%
“…This might be explained by the high free radicalscavenging activity of the DNE (Nakamura et al, 2022). In our previous study, we found that dietary supplementation with 2.0% of DNE significantly increased the expression of genes encoding antioxidant enzymes and reduced the MDA concentration in the breast muscle of broiler chickens kept under thermo-neutral temperature (Nakamura et al, 2022). Consistent with this, in the present study, the MDA concentration was higher in the breast muscle of chickens kept under cyclical HT conditions than in that of chickens kept under thermoneutral conditions (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be, however, emphasized that fresh neem leaves can negatively affect broiler growth due to their high crude fiber content [29], because of which it is necessary to add them in the form of a dry leaf extract. The results of Nakamura et al (2022) [30] showed that the addition of 2.0% neem dry extract to broiler feed increased the expression of genes important for the activity of antioxidant enzymes in the breast muscle (Cu/Zn superoxide dismutase-SOD1, Mn superoxidase-MnSOD, glutathione peroxidase 7-GPX 7 and catalase-CAT). Furthermore, the authors showed that the addition of the neem to broiler feed reduces lipid peroxidation and water losses in m. pectoralis major muscle.…”
Section: Phytonutrientsmentioning
confidence: 99%